Condicionamento osmótico e germinação de sementes de Eucalyptus pellita e Eucalyptus brassiana submetidas a déficit hídrico - Benitez, Analia Adriana Ibañez (2021)
The initial growth of forest species in the field is affected by soil water availability, therefore, this work studies the impact of water deficit on Eucalyptus pellita and Eucalyptus brassiana seeds. The adaptation of a species to a certain environment is related to the physiological characteristics of the seed lot that influence tolerance to water deficit. Thus, the objectives of this work are: To study the effect of water deficit on the imbibition and germination of Eucalyptus seeds, and to evaluate the effect of osmopriming on the germination of Eucalyptus seeds under water deficit. The experiment was conducted at the Tissue Culture Laboratory of the Faculty of Forestry Engineering, Federal University of Mato Grosso (UFMT), Campus de Cuiabá (MT). To determine the imbibition curve, it was used as substrate between germitest paper, with two sheets, moistened with water and PEG solution with osmotic potentials of -0.4; -0.8 and -1.2 MPa and stored in BOD at a temperature of 20°C. For seed germination under water deficit in PEG 6000 at osmotic potentials of 0.0; -0.2; -0.4; -0.6; -0.8 and -1.2 MPa was simulated in BOD at 25 °C and a completely randomized design (DIC) in a 2 x 6 factorial scheme (2 species x 6 water potentials) was used. For seed germination under water deficit after osmopriming, the seeds were conditioned in PEG solutions with potentials of -0.4 and -1.2 MPa for 120 hours. Water deficit was simulated in BOD at 25 °C, using PEG solutions with water potentials of 0.0; -0.2 and -0.4 MPa and the experiment was carried out in a completely randomized design (DIC) in a 2 x 2 x 3 factorial scheme (2 species x 2 conditioning x 3 water potentials). It was observed that the three-phase imbibition pattern occurs at a potential of 0.0 MPa for the two studied species, germination decreased with the increase of water restriction for the two Eucalyptus species. The species of Eucalyptus pellita has tolerance to germinate under moderate water stress between -0.2 and -0.4 MPa. Due to the physiological quality of the Eucalyptus brassiana seed lot used in this research, it was observed that it is more sensitive to water stress even after osmopriming. Seeds of both Eucalyptus species conditioned in PEG provided faster and more uniform germination when compared to unconditioned seeds.